Effect of carbon nanotubes on the bonding mechanism of non-corrosive reinforcements to concrete - Alaa, Taha (2024)
This study aimed to assess the impact of waterborne pre-dispersed multiwall carbon nanotubes (MWCNTs) at a concentration of 0.2 wt % on the bond strength between concrete and non-corrosive reinforcements, including stainless steel (SS), glass fiber reinforced polymers (GFRP), and basalt fiber reinforced polymers (BFRP) bars. Additionally, the study examined the influence of MWCNTs on the compressive and flexural tensile strengths of concrete. Various factors, including the type of reinforcement bar, concrete composition, and surface treatment of fiber-reinforced polymers (FRP) bars, were investigated to analyze their effects on bond behavior and development length. Through testing 30 pullout specimens, parameters including maximum bond strength, normalized bond strength, failure mode, and bar slippage under maximum bond stress were evaluated. Results showed a slight reduction in bond strength, minor improvement in normalized bond strength, increased development length of FRP bars, and decreased reinforcement slippage associated with the ultimate bond stress when MWCNTs were incorporated into the concrete mixture. Furthermore, the study calibrated two established analytical models, namely the CMR and BPE models, to account for the specific properties of the reinforcement bars and concrete materials used.